Formal mentoring in nonprofit organizations. Model proposition - Bortnowska Hanna; Seiler Bartosz (Management, 2019)
Mentoring is the process of exchanging knowledge, experience and values between a more and less experienced member of the organization. It is sometimes used in business entities, but according to the authors, it is worth pointing out its potential utility in the nonprofit sphere. It can contribute to increasing the efficiency of third sector organizations, both indirectly, by improving the competences of the staff, and directly - at work with the beneficiaries. The article presents a model of formal mentoring in nonprofit organizations. It consists of 11 stages and takes into account the specificity of such entities, e.g. financial constraints, a shortage of mentors familiar with the specifics of the nonprofit organizations, fears of introducing formalized techniques associated with the commercial sector, irregular work modes of volunteers and other employees of non-governmental entities organizations and the lack of time connected with it.